Demonstrating School Counselor Efficacy in Individual Interventions Using Single-Case Research Design: A Guided Process. Issue 1 (January 2020) - Sowell, Shaun M.; Hunter, Quentin; Richey, Katelyn Gosnell; Baxter, Christopher
School counselors are tasked with many activities, including demonstrating the effectiveness of interventions they use with students. The American School Counselor Association recommends that school counselors include assessment, appraisal, and evaluation of delivery and program management in their school counseling program. Single-case research design is a data collection and analysis strategy that can assist school counselors with this task. We developed the Impact of Intervention tool to provide school counselors a tool to streamline the data collection process.